2019
DOI: 10.1080/09638288.2019.1685602
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors are more strongly associated with pain than radiographic severity in non-invasively treated first carpometacarpal osteoarthritis

Abstract: Background: The aim of this study was to investigate to what extent psychological factors are related to pain levels prior to non-invasive treatment in patients with osteoarthritis of the first carpometacarpal joint. Methods: We included patients (n ¼ 255) at the start of non-invasive treatment for osteoarthritis of the first carpometacarpal joint who completed the Michigan Hand Outcome Questionnaire. Psychological distress, pain catastrophizing behavior and illness perception was measured. X-rays were scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…One study found that this difference could be explained by the difference in pain-related anxiety 33 . This hypothesis is supported by an analysis by Hoogendam et al 34 in CMC1 OA, who reported that psychosocial factors are associated with pain, but not the radiographic severity. Studying which factors determine if patients seek care for symptomatic thumb base OA could provide clinicians with an opportunity to simultaneously treat this underlying disease processes alongside the changes in bone morphology.…”
Section: Osteoarthritis Andcartilagementioning
confidence: 60%
“…One study found that this difference could be explained by the difference in pain-related anxiety 33 . This hypothesis is supported by an analysis by Hoogendam et al 34 in CMC1 OA, who reported that psychosocial factors are associated with pain, but not the radiographic severity. Studying which factors determine if patients seek care for symptomatic thumb base OA could provide clinicians with an opportunity to simultaneously treat this underlying disease processes alongside the changes in bone morphology.…”
Section: Osteoarthritis Andcartilagementioning
confidence: 60%
“…However, in these studies post-treatment PROMs were not adjusted for pre-treatment PROMs, which might explain the difference with our own findings. As CMC-1 OA complaints are known to be associated with pain catastrophizing and psychological distress before treatment [38], it may be worthwhile to further investigate potential indirect pathways through which these mindset variables affect treatment outcomes in CMC-1 OA.…”
Section: Discussionmentioning
confidence: 99%
“…People with hand OA frequently seek medical care due to ongoing pain and disability [ 3 ]. It is therefore important to improve our ability to identify and classify different types of pain in order to develop more effective treatment plans [ 4 ].…”
Section: Introductionmentioning
confidence: 99%